(3cfR GdMceGA heWdH GdCWHGAs - (3CHh SYjO Hf EHQGgje GdeJWHH GdeYQjs
(3ChdgG (B:s
(3GddhM GdChd ai GdCOhjI GdJi JfaY ef LejY GfhGY GdUOGY , GdHfaSLjfaY ef GdUOGY GdMGO TQHkG hVeGOkG CSdhH MeO ddUOGY GdMGO s
(3BNQgG (B:s
(3GddhM (B148 (3aj GdCOhjI GdMGdjIGdebheI GdefHKbI, Gdec GdNTdNT YfH GdKYdH GdThcQGf GdSGPL ajg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdChdis
(3fSNI MOjKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B210 s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGj (B(1/4601) s
Keywords: (3GdWHs